Heat extraction performance and formation cooling effect of borehole heat exchangers in high-temperature coal mines - Jinkui Zhang; Delong Meng; Xiang Sun; Wenliang Sun; Qiang Li; Lihan Chen; Chaofan Chen; Chaofan Chen; Boyan Meng; Wanlong Cai; Yanlong Kong (Frontiers in Built Environment)
High-temperature coal mines represent a promising but underexplored source of geothermal energy that can be harnessed for sustainable heating and cooling. This study evaluates the performance of borehole heat exchangers (BHEs) in active high-temperature coal mines, with a focus on their heat extraction capabilities and the associated formation cooling effects. A coupled three-dimensional numerical model is developed using OpenGeoSys to simulate heat transport processes within a network of five tunnel boreholes. The model is validated against analytical solutions and a one-dimensional wellbore simulator. Results show that the peripheral and central BHEs can reach a stable heat extraction rate of 7,975 and 7,950 W after 120 days, respectively, indicating that the heat extraction capacity is almost unaffected by thermal interactions between the tunnel boreholes in the short term. However, when colder water is injected into the tunnel wells, more heat can be extracted and the formation temperature will decrease faster, leading to a more significant thermal interaction between the well and a more pronounced cooling effect. Groundwater flow further alters these dynamics by redistributing heat within the subsurface and affecting the thermal interaction among boreholes. These findings highlight the dual potential of BHE systems in coal mines to both supply geothermal energy and mitigate underground heat hazards, providing practical insights for integrating such systems into district heating networks in mining regions.